Comparison of the Tongue-Palate Pressure Patterns According to the Tongue Pressure in Community-Dwelling Older Adults - Min-Ji Jo; Soo-Min Kim; Seong-Chan Park; Hye-Jin Park; Yun-Seon Lee; Tae-Woo Kim; Ji-Seon Hong; Eui-Yeon Lee; Sung-Hoon Kim; Sun-Young Han (The Korean Society of Dental Hygiene Science, 2023)
Background: Oral frailty has garnered considerable interest following its identification as a risk factor for physical frailty. The Korean oral frailty diagnosis criteria have emphasized the need for extensive research on oral frailty diagnostic items and interventions. Our study performed an in-depth analysis of the tongue-palate pressure patterns in healthy community-dwelling older adults. Methods: Of the 217 older adults aged ≥60 years who visited a senior center in Wonju, 205 participants who completed tongue pressure measurement were included in the final analysis. Pressure changes over time were recorded by instructing the participants to press their tongue against the hard palate with for 7 seconds per cycle. The participants were divided into the normal and abnormal tongue pressure (NTP and ATP, respectively) groups based on whether they achieved the target tongue pressure at least once; tongue pressure patterns were compared between the groups. Furthermore, the average time taken to achieve the standard tongue pressure value was calculated for the participants in the NTP group and used to evaluate the decrease in tongue pressure in the ATP group. Results: Among the 205 participants, 40.5% had ATP. The tongue pressure graph revealed a gentle and consistent incline that was maintained even after achieving standard tongue pressure in the NTP group. The graph was more extreme in the ATP group, and the changes in the pressure type varied across individuals; the tongue pressure was only 48.4%, 40.7%, 31.9%, and 22.6% of the NTP in the participants in their 60s, 70s, 80s, and ≥90s, respectively (p＜0.05). Conclusion: Tongue pressure weakness was observed in 40.5% of the healthy community-dwelling older adults. Furthermore, ATP graphs were observed in the patients with tongue pressure weakness. Thus, activities improving the oral function in community-dwelling older adults and systematic oral rehabilitation programs should be devised to promote normal swallowing.